Low operating voltage resistive random access memory based on graphene oxideepolyvinyl alcohol nanocomposite thin films - Ngo, Huu Thoai (H. : ĐHQGHN, 2020)
A high-performance non-volatile memory with low power consumption for long battery life and for large data storage is one of the key requirements of the wearable and other electronic Internet of Things (IoT) devices. In this study, we have fabricated and investigated the resistive switching behavior of an RRAM device using the nanocomposite of polyvinyl alcohol (PVA) and graphene oxide (GO) as the switching layer in a hybrid Ag/PVAeGO/FTO structure. The resistive switching behavior of the hybrid Ag/PVAeGO/ FTO device depends on the GO amount in the PVAeGO matrix. The optical analysis depicts the good interaction through the hydrogen bonds between the hydroxyl group (eOH) of PVA and C]O of GO which play an important role in lowering the power consumption (sweeping voltage 0.5 V to þ0.5 V, VSET ¼ 0.28 V, VRESET ¼ 0.34 V, switching ratio ION/IOFF ¼ 104) and switching mechanism of the hybrid Ag/PVAe0.5 wt% GO/FTO device compared to the Ag/PVA/FTO, Ag/GO/FTO and Ag/PVAe1.0 wt% GO/FTO devices. The electrical conduction mechanism is found dominant by the SCLC and the Ohm's law corresponding to the high and low resistance states in which the combination of the trap filling and the delocalization of electrons within p bonding rings switch the device from the high to the low resistance state.